Factors Affecting The Incidence of Anemia in Pregnant Women at Rumbio Public Health Center, Kampar Regency: Multivariate Analysis - Lubis, Erlinawati; Anggriani Harahap, Dewi; Anggraini Dhilon, Dhini (Window of Health : Jurnal Kesehatan, 2025)
According to the WHO in 2014, as many as 40% of maternal deaths in developing countries are related to anemia in pregnancy. The prevalence of anemia in Indonesia is 50.9% among pregnant women. In Riau Province, the incidence of anemia among pregnant women is still relatively high at 37.1%. In Kampar Regency, the rate of anemia among pregnant women in 2016 was 16.03%, while in 2017 it rose to 32.59%. This study aims to analyze multivariate factors that cause the incidence of anemia in pregnant women at Rumbio Public Health Center, Kampar Regency. This type of research is quantitative analytic with a cross-sectional design. This study was conducted in March 2023 with a population of 385 pregnant women and a sample size of 78 people. The sampling technique used was purposive sampling. Bivariate and multivariate data analysis using chi-square statistical tests and logistic regression multivariate analysis. The results of bivariate analysis indicate that nutritional status, parity, and socio-economic variables are not significantly associated with anemia (p value> α 0.05), while the variables adherence to taking Fe tablets and age are significantly associated with anemia (p value < α 0.05). The results of multivariate analysis showed that the variable of adherence to taking Fe tablets was significant to anemia because the p value < 0.05, while the independent variable of age was not significant to anemia because the p value > 0.05. The OR value of adherence to taking Fe tablets is 67, meaning that people who are not adherent are more at risk of developing anemia. In conclusion, the variable of adherence to taking tablets is the variable most associated with the incidence of anemia in pregnant women. It is expected of pregnant women to be obedient and on time in taking Fe tablets to avoid the incidence of anemia in pregnancy.